Development of efficient and stable catalytic systems for polyolefin plastic waste upcycling - Wang, H (2024)
While the widespread use of plastics has greatly benefited modern life, it has also led to significant environmental, health, social, and economic challenges due to poor waste management and low recyclability. Traditional disposal methods, such as landfilling and incineration, are energy-intensive and environmentally damaging. Recent advancements in catalytic technologies, including hydrocracking, hydrogenolysis, and metathesis, offer more sustainable approaches by converting polyolefin (PO) plastic waste into valuable products under milder conditions with lower emissions. However, more efficient and stable catalytic approaches are required to meet the demands of industrial-scale applications.